2013
DOI: 10.1016/j.ultsonch.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-intensified laccase production from Trametes versicolor

Abstract: a b s t r a c tAn efficient intermittent ultrasonic treatment strategy was developed to improve laccase production from Trametes versicolor mycelia cultures. The optimized strategy consisted of exposing 2-day-old mycelia cultures to 5-min ultrasonic treatments for two times with a 12-h interval at the fixed ultrasonic power and frequency (120 W, 40 kHz). After 5 days of culture, this strategy produced the highest extracellular laccase activity of 588.9 U/L among all treatments tested which was 1.8-fold greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…El Ghaouth et al [10] reported the leakage of chitin deacetylase, amino acids and proteins through the chitosan-damaged cell wall of Rhizopus stolonifer. Increase in the porosity of the cell wall of T. versicolor and higher extracellular laccase activity in response to ultrasonic treatment have been reported [17].…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…El Ghaouth et al [10] reported the leakage of chitin deacetylase, amino acids and proteins through the chitosan-damaged cell wall of Rhizopus stolonifer. Increase in the porosity of the cell wall of T. versicolor and higher extracellular laccase activity in response to ultrasonic treatment have been reported [17].…”
Section: Resultsmentioning
confidence: 91%
“…Chitosan has been reported to induce higher synthesis of cell wall-associated enzymes, phenolic compounds, amino acids and some secondary metabolites in fungi [31,32]. Laccase secretion in filamentous fungi can be enhanced by lots of factors, which range from availability of saprophytic nutrients to morphological changes [17,33]. Chitosan could have facilitated increased synthesis of intracellular laccase and its efflux, thereby increasing the laccase activity in the medium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations